A 20-year experience of electron microscopy in the diagnosis of primary ciliary dyskinesia - Jean‐François Papon; A. Coste; Françoise Roudot‐Thoraval; M. Boucherat; G. Roger; Aline Tamalet; Anne-Marie Vojtek; Serge Amselem; Estelle Escudier (2009)
Transmission electron microscopy (TEM) analysis of ciliary ultrastructure is classically used for the diagnosis of primary ciliary dyskinesia (PCD). We report our extensive experience of TEM analysis in a large series of patients in order to evaluate its feasibility and results. TEM analysis performed in 1,149 patients with suspected PCD was retrospectively reviewed. Biopsies (1,450) were obtained from nasal (44%) or bronchial (56%) mucosa in children (66.5%) and adults (33.5%). TEM analysis was feasible in 71.4% of patients and showed a main defect suggestive of PCD in 29.9%. TEM was more feasible in adults than in children, regardless of the biopsy site. Main defects suggestive of PCD were found in 76.9% of patients with sinopulmonary symptoms and in only 0.4% of patients with isolated upper and 0.4% with isolated lower respiratory tract infections. The defect pattern was similar in children and adults, involving dynein arms (81.2%) or central complex (CC) (18.8%). Situs inversus was never observed in PCD patients with CC defect. Kartagener syndrome with normal ciliary ultrastructure was not an exceptional condition (10.2% of PCD). In conclusion, TEM analysis is feasible in most patients and is particularly useful for PCD diagnosis in cases of sinopulmonary syndrome of unknown origin.